Text-close thick translations in two English versions of Laozi - Huang, Weixing; Hoon, Ang Lay; Hiong, Ser Wue; Jujar Singh, Hardev Kaur (Taylor & Francis, 2019)
Laozi is the most translated Chinese text. It has profound philosophical thoughts and is written in a pithy style. It is essential to present its cultural, social, and historical contexts to target readers for a deep understanding of Laozi translations. Thick translation, which aims to produce thick contextualized texts, had been adopted by Lin Yutang and Roger Ames & David Hall in Laozi translations. This qualitative study compares text-close thick translations in these two English versions in an attempt to reveal how text-close thick translations support to achieve thick contextualization. This comparison identifies similarities and differences of subtitles, notes, commentaries, and supplementary material. The findings show that notes and commentaries are translators’ favorite maneuvers in supplying contextual information. However, due to the translators’ different backgrounds, attention is paid to different aspects. In conclusion, translators can employ different means of text-close thick translations to construct thick contexts, thereby enhancing target readers’ understanding.